Effect of coping strategies on psychological disorders: An SEM Analysis - Merma Paricahua, Mauro (2025)
Objective: to know the explanatory potential of coping strategies on the symptoms of psychological disorders in Peruvian university students in the context of COVID-19. Methodology: quantitative with a structural equation model. The multidimensional coping strategies inventory COPE and the self-report questionnaire of symptoms of mental disorders SRQ were applied to 699 university students. Results: Three explanatory models were developed; the second model was considered because it obtained better goodness-of-fit indices. This model reflects that symptoms of psychological disorders are explained by avoidance strategies, as they are risk factors. Coping strategies are protective of psychological disorders, being moderately linked with strategies oriented to social and emotional well-being.